Strategy for Strengthening Research Management in Research and Community Service Institute of Parahyangan Catholic University for Research Fund from Goverment - Sutanto, Hendry William; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2013)
the object of this final project is Research and Community Service Institute in Parahyangan Catholic University. Themain issue in this final project is dealing with research funds from government.Research funds from government are increasing in the past four years, so that it needs strategy to strengthen research management in Parahyangan Catholic University. The purpose of this final project itself is to develop an appropriate strategy to strengthen research management and evaluate the current procedure of the research management. First, in developing an appropriate strategy, used gap analysis by ISO 9001 to analyze the current situation and what need to be done to fulfill the requirement in ISO 9001. After analyzing, the next step is developing a business model of the research management. The last step is making the ideal business process for this research management. From the analysis using ISO 9001, the conclusion is research management still has no meet the requirement in ISO 9001. So, it needs to improve the procedure, documentation, etc. After developing the strategy, an implementation plan needed to make the strategy came true. Some implementation plans include organization restructuring, establish a new application for this kind of research management (external funding), and socialize to research teams. All this plan is hoped can be executed by May 2013. Â Keywords: research management strategy, government funds, research and community service institute